On extreme tournaments for two types of generalized exponents - Ye, Xuemei, (Utilitas Mathematica, 2009)
We obtain complete characterizations of the extreme digraphs attaining the largest values of the two generalized exponent sets E1(n,k) and E2(n,k) for tournaments, respectively.